2016
DOI: 10.3349/ymj.2016.57.5.1185
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Oral Enteral Nutrition in Pediatric Crohn's Disease: A Single Center Non-Comparative Retrospective Study

Abstract: PurposeExclusive enteral nutrition (EEN) therapy effectively induces clinical remission in Crohn's disease (CD). It remains unclear, however, whether partial enteral nutrition (PEN) can maintain remission. This study was performed to determine the abilities of oral EEN and oral PEN to induce and maintain clinical remission in pediatric patients with CD, respectively.Materials and MethodsPediatric patients with CD who received oral EEN at a single center in 2000–2014 were identified retrospectively. Remission r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…This was either 6 or 8 weeks, apart from one study that prescribed treatment for 4 weeks (40) The 4-week EEN protocol showed the lowest percentage of remission achieved (44%), with the highest rates of remission noted in a study applying an 8-week protocol (31) in which up to 90% of patients entered remission, although it was noted that the mean time until remission was only 6 weeks, with patients having been assessed every week. This was supported by the results obtained by Kim et al (33) who also found positive results on a 6-week protocol, with 88% of patients entering remission by this point. Unfortunately, a direct comparison of remission rates grouped to treatment duration was not possible, with all studies differing too significantly in other aspects of EEN protocol design.…”
Section: Duration Of Treatmentsupporting
confidence: 80%
See 3 more Smart Citations
“…This was either 6 or 8 weeks, apart from one study that prescribed treatment for 4 weeks (40) The 4-week EEN protocol showed the lowest percentage of remission achieved (44%), with the highest rates of remission noted in a study applying an 8-week protocol (31) in which up to 90% of patients entered remission, although it was noted that the mean time until remission was only 6 weeks, with patients having been assessed every week. This was supported by the results obtained by Kim et al (33) who also found positive results on a 6-week protocol, with 88% of patients entering remission by this point. Unfortunately, a direct comparison of remission rates grouped to treatment duration was not possible, with all studies differing too significantly in other aspects of EEN protocol design.…”
Section: Duration Of Treatmentsupporting
confidence: 80%
“…In total, 16 studies met the inclusion criteria, with the key findings being summarised in Table 3. The majority of the studies identified were of a retrospective design, including three cohort studies (27)(28)(29) and eight uncontrolled cohort/case series studies (30)(31)(32)(33)(34)(35)(36)(37) The remaining five studies were prospective studies and included four RCTs (38)(39)(40)(41) and one uncontrolled study (42) Overall, the quality of studies included in this systematic review was weak, with 11 studies being rate as poor or very poor quality once study type was taken into consideration, with noncontrolled studies receiving a lower overall rating. Three studies were considered to be of moderate quality and one identified as good/high quality overall.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…47 A single center retrospective study evaluating PEN after inducing remission with EEN in pediatric patients revealed that among 58 patients (out of 66) who were continued on PEN, only forty-three patients were adherent and cumulative remission rates at 1 and 2 years were 67% and 52% respectively. 48 …”
Section: Dietmentioning
confidence: 99%